Allozyme electrophoretic methods for analyzing genetic variation in giant clams (Tridacnidae) - Benzie, J.A.H.; Williams, S.T.; Macaranas, J.M. (Camberra, Australia ACIAR, 1993)
ACIAR Technical Reports, 23
Keywords: Tridacnidae; Electrophoresis; Giant clams--Sample collection and storage; Giant clams--Isoenzyme analysis